Flexible Working Arrangement (FWA) Model: Reducing Congestion Levels, Work Stress, and Increasing Work Productivity - Sultan, Zulkifli (Jurnal Manajemen Bisnis, 2024)
Research aims:  This research aims to analyze the impact of the flexible working arrangement (FWA) system in reducing traffic jams, reducing work stress, and increasing employee work productivityDesign/Methodology/Approach: This research was carried out using a sample collection technique using purposive sampling by distributing questionnaires to 100 government employees and company employees and interviewing 5 informants from government employees.  Data analysis uses SEM (structural equation model) with the AMOS analysis tool.Research findings: Based on the results of the research and discussion, it can be concluded that flexible working arrangements (FWA) have an important role in reducing traffic jams, and traffic jams have the impact of increasing a person's work stress. Meanwhile, reducing traffic congestion has a positive impact on workers, work stress can also decrease. Despite flexible working arrangements (FWA), work congestion and stress do not influence work productivityTheoretical Contribution/Originality: This research contributes to the science of human resource management. Apart from that, insight into urban management related to HR work activities.Practitioners/Policy Implications:  The results of this research are a source and basis for guidance in structuring work patterns that are more efficient and effective, working flexibly can reduce the level of traffic congestion.Research Limitations/Implications: There are many limitations to this research and future researchers must explore it more deeply, especially the very limited number of respondents and informants who cannot be met directly so the question-and-answer process is less in-depth. Apart from the respondents and informants, because the indicators in this research for each variable are still lacking, the references are still weak